Antarctic Theatricals: The Frozen Farce of Scott's First Expedition - Elizabeth Leane (2003)
For over fifty years, a large, frozen heap of rubbish rested against the western wall of Discovery Hut, Ross Island, Antarctica. The hut was constructed in 1902 by members of the 1901-04 British National Antarctic Expedition led by Robert Falcon Scott. The men who used the hut -not only those aboard the Discovery, but also members of several later expeditions--had used the western window as a convenient garbage chute.